2016
DOI: 10.1080/02640414.2016.1211311
|View full text |Cite
|
Sign up to set email alerts
|

Gross motor coordination in junior tennis players

Abstract: The purpose of this study was twofold: (1) to determine the gross motor coordination performance levels of junior tennis players and (2) to analyse the effects of age and gender. Participants were junior male (n = 50) and female (n = 51) tennis players aged 6-14. Körperkoordinationstest für Kinder (KTK) was used to assess the gross motor coordination of the participants. Results revealed that none of the participants performed lower than normal level in motor coordination. Besides, 40.6% of the participants pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 14 publications
1
25
0
5
Order By: Relevance
“…Another group of authors confirmed that sport-specific training could improve motor coordination characteristics in children but it depends on the sport in which they are enrolled [39]. Regarding gender differences, one interesting study in young tennis players showed that when the children are trained equally, motor coordination is not a significant predictor that could differentiate genders [40]. Additionally, Haugen et al [41] showed that children with higher levels of motor coordination maintain higher levels of motor coordination and physical fitness throughout childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Another group of authors confirmed that sport-specific training could improve motor coordination characteristics in children but it depends on the sport in which they are enrolled [39]. Regarding gender differences, one interesting study in young tennis players showed that when the children are trained equally, motor coordination is not a significant predictor that could differentiate genders [40]. Additionally, Haugen et al [41] showed that children with higher levels of motor coordination maintain higher levels of motor coordination and physical fitness throughout childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the paucity of investigations about the topic, it is difficult to compare our results with other studies. While the degree of motor coordination seems to be an important predictor of motor performance in different sports [12][13][14][15][16][17][18], little is known about this relationship in volleyball. Specifically in volleyball, Pion et al [19] found that high-level young female players had better motor coordination compared with their average-level peers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relationship has also been investigated between the degree of motor coordination and performance in different sports [11], such as tennis [12,13], table tennis [14], soccer [15], gymnastic [16,17], judo [18], and volleyball [19]. Overall, these findings have suggested that the degree of motor coordination is an important predictor of sports performance in youth athletes.…”
Section: Introductionmentioning
confidence: 98%
“…[18][19][20] Afterwards, motor competence remains relatively stable throughout adolescence. 16,21 Considering this stability and the foundational nature of general motor competence for sport-specific motor skills, 16 it has the potential to be a useful tool in the talent pathway.…”
Section: Introductionmentioning
confidence: 99%